1933
DOI: 10.1021/j150347a004
|View full text |Cite
|
Sign up to set email alerts
|

Refractivities of Liquid Compounds of Phosphorus.

Abstract: The number of compounds of phosphorus hitherto examined refractometrically is small, the only investigator of an homologous series of such substances being Kowalewski (1). The present work has been undertaken with a view to extension of our knowledge in this field, particularly with respect to types of compounds and their number.The first to determine the atomic refractivity of phosphorus was Haagen (2), who from measurements on phosphorus trichloride with C light, deduced the value 14.93, in terms of the Glad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1948
1948
2004
2004

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Therefore, for P the higher molar refraction per polarizability presumably expresses the stronger propensity of nonbonding electrons to be polarized by an applied electric field. Previous studies of phosphorus compounds showed that their molar refractivity strongly depends on P valency. , …”
Section: Resultsmentioning
confidence: 99%
“…Therefore, for P the higher molar refraction per polarizability presumably expresses the stronger propensity of nonbonding electrons to be polarized by an applied electric field. Previous studies of phosphorus compounds showed that their molar refractivity strongly depends on P valency. , …”
Section: Resultsmentioning
confidence: 99%
“…Jones et al (11) determined the density and refractive index of tetraethyl pyrophosphate, which they evidently succeeded in preparing by the Arbuzovs' complex reaction (1). They calculated the molecular refraction by both the Gladstone-Dale and Lorenz-Lorentz equations.…”
Section: Tetraethyl Pyrophosphatementioning
confidence: 99%